Is there a “Dark Side” to Monitoring? Board and Shareholder Monitoring Effects on M&A Performance Extremeness - Goranova, Maria L.; Priem, Richard L.; Ndofor, Hermann A.; Trahms, Cheryl A. (Strategic Management Journal, 2017)
[Research summary: We investigate the effects of monitoring by boards of directors and institutional shareholders on merger and acquisition (M&A) performance extremeness using a sample of M&A deals from 1997 to 2006. Both governance research and legal reforms generally have espoused a “raise all boats” view of monitoring. We instead investigate whether monitoring may serve as a double-edged sword that limits CEO discretion to undertake both value-destroying M&A deals and value-creating ones. Our findings indicate that the relationship between monitoring and M&A performance is more complex than previously believed. Rather than “raising all boats” in a shift towards better M&A outcomes, monitoring instead is associated with lower M&A losses, but also with lower M&A gains. Managerial summary:Mergers and acquisitions (M&As) are a quintessential corporate activity. There were $3.8 trillion worth of M&A deals in 2015, despite scholars and practitioners reporting that M&As often perform poorly. We question the widespread belief that more vigilant monitoring by boards of directors and large shareholders will raise M&A performance, overall. Put differently, does monitoring constrain CEOs’ discretion to pursue bad deals, while simultaneously encouraging them to pursue good ones? We find that monitoring limits both large M&A losses and large M&A gains. Contrary to widely held beliefs, our results indicate that constraining executives’ ability to pursue value-destroying M&A deals does not simultaneously encourage or enable CEOs to pursue value-creating deals.]